Car service booking system (CSBS) / Syahrul Soubry Ridzuan - Ridzuan, Syahrul Soubry (2014)
Current manual system to handle booking process of Car Service Centre is believed to be cost and time consuming, and requires a lot of documentation. The usage of the web-based system and online reservation are currently dominating the modern information technology which give many advantages to people. Thus, the car booking service system (CSBS) is presented to facilitate the booking process for car service. The system is expected to be used as a tool to manage booking and conduct booking respectively. CSBS is developed by following the WATERFALL methodology which comprises of Analysis, Design, Development, Implementation and Evaluation phases. For the project, another phase has been added which is Documentation. The evaluation of the system has been conducted which focuses on the user interface satisfaction, system usability, system effectiveness and system efficiency. Based on the result, it shows that the user interface, usability, effectiveness and efficiencies had satisfied the target user with the highest mean are 4.3333, 4.3000, 4.5000 and 4.4333 respectively. However, the system still need to be improved in the future to make it more effective, interactive, usable and more efficient.